Accountability protocols? On-chain dynamics in blockchain governance - Kelsie Nabben; Primavera De Filippi (Internet Policy Review, 2024)
Accountability refers to a relationship of responsibility, answerability, and enforceability between individuals and groups. In contrast to traditional institutions that rely on enforcement of accountability through traditional legal frameworks, blockchain systems rely on the "rule of code", i.e. the operation, governance, and transactions on a blockchain are governed by pre-written, transparent, and immutable rules that are expressed in software code. By empirically examining the case of the Ethereum blockchain and the Lido "liquid" staking services protocol, this paper analyses the formalisation of accountability mechanisms between protocols to ensure that Lido's proportionate share of staked ETH on the network does not pose a risk to the security and stability of Ethereum. The findings of this paper are threefold: (1) accountability on a blockchain is achieved through the implementation of checks and balances institutionalised via technological protocols ("on-chain accountability"); (2) accountability requires trade-offs, meaning that giving accountability to one type of stakeholders might actually reduce the accountability of the system for another category of stakeholder; and (3) end users of the blockchain are consumers of accountability, rather than influential participants in producing it. This research underscores the complex interplay of technical and governance considerations in ensuring accountability within blockchain systems, offering insights into the broader implications of on-chain accountability for stakeholders across blockchain ecosystems.
Keywords: 300; Blockchain; Accountability; Governance; Rule of code; Design